Ocean warming ameliorates the negative effects of ocean acidification on Paracentrotus lividus larval development and settlement. (September 2015) - García, Eliseba; Clemente, Sabrina; Hernández, José Carlos
Abstract: Ocean warming and acidification both impact marine ecosystems. All organisms have a limited body temperature range, outside of which they become functionally constrained. Beyond the absolute extremes of this range, they cannot survive. It is hypothesized that some stressors can present effects that interact with other environmental variables, such as ocean acidification (OA) that have the potential to narrow the thermal range where marine species are functional. An organism's response to ocean acidification can therefore be highly dependent on thermal conditions. This study evaluated the combined effects of predicted ocean warming conditions and acidification, on survival, development, and settlement, of the sea urchin Paracentrotus lividus . Nine combined treatments of temperature (19.0, 20.5 and 22.5 °C) and pH (8.1, 7.7 and 7.4 units) were carried out. All of the conditions tested were either within the current natural ranges of seawater pH and temperature or are within the ranges that have been predicted for the end of the century, in the sampling region (Canary Islands). Our results indicated that the negative effects of low pH on P. lividus larval development and settlement will be mitigated by a rise in seawater temperature, up to a thermotolerance threshold. Larval development and settlement performance of the sea urchin P. lividus was enhanced by a slight increase in temperature, even under lowered pH conditions. However, the species did show negative responses to the levels of ocean warming and acidification that have been predicted for the turn of the century. Highlights: We assessed combined effects of ocean temperature and pH on sea urchin larval cycle. Experimental climatic scenarios covered present and future natural variability. Responses on different life stages of Paracentrotus lividus were investigated. Moderate warming counteracted the negative effects of acidification on early stages. Findings provide a general view of the responses of sea urchins to future scenarios.